Defining Islamic Transnationalism: A Case Study of Indonesia’s Nahdlatul Ulama - Vyan Tashwirul Afkar; Dwi Ardhanariswari Sundrijo (Global Strategis, 2023)
This article examines Nahdlatul Ulama (NU) as a transnational actor in international relations and comprehends its behavior based on the dimensions of Transnational Islam. NU is well recognized as an Indonesian national religious civil society organization and presented itself as the antithesis of Transnational Islam in the country. Meanwhile, NU conducts many cross-border activities, has members all over the world, and has offices based in various countries, enough to make it be perceived as a Transnational Islamic organization. This article examines why NU is a Transnational Islamic organization using Bowen's three dimensions of Transnational Islam: demographic movements, transnational religious institutions, and Islamic references and debates. This research applies qualitative descriptive methods from literary works. This research concludes that NU is a Transnational Islamic organization as it fits all three of Bowen's dimensions. NU's transnational dimensions are found at various but interconnected categories, specifically cultural, structural, and ideational levels. Keywords: Nahdlatul Ulama, Indonesia, Islam, Islamic Transnationalism, Transnationalism   Artikel ini menguji status Nahdlatul Ulama (NU) sebagai aktor transnasional di dalam hubungan internasional dan menjabarkan perilakunya berdasarkan dimensi Islam transnasional. NU telah dikenal sebagai organisasi keagamaan Islam di Indonesia dan menampilkan diri sebagai antitesis gerakan-gerakan Islam transnasional di dalam negeri. Sementara itu, NU sendiri melakukan banyak kegiatan lintas batas negara, memiliki keanggotaan dari berbagai belahan dunia, dan memiliki kepengurusan internasional, sehingga dianggap cukup untuk menyebut NU sebagai organisasi Islam transnasional. Artikel ini berargumen bahwa NU adalah organisasi Islam transnasional berdasarkan tiga dimensi yang dikemukakan Bowen: demographic movements, transnational religious institutions, dan Islamic reference and debates. Artikel ini disusun dengan pendekatan kualitatif deskriptif melalui penelusuran pustaka. Kesimpulan penelitian ini menunjukkan bahwa NU adalah organisasi Islam transnasional karena sesuai dengan ketiga dimensi Bowen. Adapun dimensi transnasionalitas NU berada di tiga level berbeda yang saling berkaitan, yaitu di level kultural, struktural, dan ideasional. Kata-kata kunci: Nahdlatul Ulama, Indonesia, Islam, Islam Transnational, Transnationalisme